Assessing the Efficacy of a Family-Based Juvenile Court Intervention - Chlebuch, Natasha (Journal of contemporary criminal justice, 2025)
A proliferation of parent and family-oriented interventions has emerged within the field of juvenile justice, aiming to reduce youth offending through better parenting practices. While there is robust evidence for the efficacy of a few model programs, many family interventions have received less empirical attention despite mixed evidence on their efficacy. This study aims to assess the efficacy of a voluntary parenting program (Family Support Services; FSS) for parents of youth on juvenile probation in a Midwestern state over the span of 15 years (N = 1,844). Analyses reveal that after controlling for robust predictors of recidivism, FSS was not associated with a decrease in recidivism but rather youth whose parents participated in FSS were more likely to recidivate compared with youth of non-FSS parents. Further moderating analysis found that the iatrogenic association was stronger for low-risk youth.